Strategi Pembelajaran Bahasa Siswa EFL Pada Kelas Argumentative Writing di UNIROW Tuban - Iqlima, Putri Amifalahiya; Sofia, Rissa; Triassanti, Risa; Panggabean, Christina Innocenti Tumiar (Universitas Nusantara PGRI Kediri, 2023)
The focus of this research is on EFL students’ language learning strategies used in Argumentative Writing class at UNIROW Tuban. It sought to determine the students’ most frequent language learning strategies and the strategies’ distinctions between students, both male and female. The descriptive qualitative was employed as the design of research for this study. The study's participants are 15 EFL students enrolled in Argumentative Writing class from English Language Education department undergraduate program of UNIROW Tuban. The questionnaire and interview data were qualitatively examined using Oxford's (1990) theories of language learning. It was identified that there were six kinds of language learning strategies used by the students, namely memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies, and social strategies. The findings showed that in the Argumentative Writing class, both genders of students most frequently employed cognitive strategies (30,1%). Additionally, it was discovered that female students (23,5%) employed more varied language learning strategies than male students (22,5%). The cognitive strategies appear to be the finest support strategies employed in Argumentative Writing class that can overcome students' writing limitations.